A Rayleigh-Ritz approach for postbuckling analysis of variable angle tow composite stiffened panels. (February 2018) - Oliveri, V.; Milazzo, A.
Highlights: A Rayleigh-Ritz approach for post-buckling analysis of variable angle tow composites is proposed. Stiffened panels are modelled by a domain decomposition method and penalty techniques. General symmetric and non-symmetric lay-ups can be investigated. Post-buckling regime for variable angle tow stiffened composite plates is addressed for the first time. The obtained results show the applicability and effectiveness of the approach. Abstract: A Rayleigh-Ritz solution approach for generally restrained multilayered variable angle tow stiffened plates in postbuckling regime is presented. The plate model is based on the first order shear deformation theory and accounts for geometrical nonlinearity through the von Kármán's assumptions. Stiffened plates are modelled as assembly of plate-like elements and penalty techniques are used to join the elements in the assembled structure and to apply the kinematical boundary conditions. General symmetric and unsymmetric stacking sequences are considered and Legendre orthogonal polynomials are employed to build the trial functions. A computer code was developed to implement the proposed approach and to establish its applicability and its features for investigating variable angle tow structures. The proposed solution is validated by comparison with literature and finite elements results. Original results are presented for postbuckling of variable angle tow stiffened plates showing the potentialities of the method.